Coagulation factor XI improves host defence during murine pneumonia-derived sepsis independent of factor XII activation - Stroo, Ingrid; Zeerleder, Sacha; Ding, Chao; Luken, Brenda M.; Roelofs, Joris J. T. H.; de Boer, Onno J.; Meijers, Joost C. M.; Castellino, Francis J.; van ’t Veer, Cornelis; van der Poll, Tom (Thrombosis and Haemostasis, 2017)
Bacterial pneumonia, the most common cause of sepsis, is associated with activation of coagulation. Factor XI (FXI), the key component of the intrinsic pathway, can be activated via factor XII (FXII), part of the contact system, or via thrombin. To determine whether intrinsic coagulation is involved in host defence during pneumonia and whether this is dependent on FXII activation, we infected in parallel wild-type (WT), FXI knockout (KO) and FXII KO mice with two different clinically relevant pathogens, the Gram-positive bacterium Streptococcus pneumoniae and the Gram-negative bacterium Klebsiella pneumoniae, via the airways. FXI deficiency worsened survival and enhanced bacterial outgrowth in both pneumonia models. This was accompanied with enhanced inflammatory responses in FXI KO mice. FXII KO mice were comparable with WT mice in Streptococcus pneumoniae pneumonia. On the contrary, FXII deficiency improved survival and reduced bacterial outgrowth following infection with Klebsiella pneumoniae. In both pneumonia models, local coagulation was not impaired in either FXI KO or FXII KO mice. The capacity to phagocytose bacteria was impaired in FXI KO neutrophils and in human neutrophils where activation of FXI was inhibited. Deficiency for FXII or blocking activation of FXI via FXIIa had no effect on phagocytosis. Taken together, these data suggest that FXI protects against sepsis derived from Streptococcus pneumoniae or Klebsiella pneumoniae pneumonia at least in part by enhancing the phagocytic capacity of neutrophils by a mechanism that is independent of activation via FXIIa.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Factor XI; factor XII; Klebsiella pneumoniae; Streptococcus pneumoniae; pneumonia